Influences of Island Characteristics on Plant Community Structure of Farasan Archipelago, Saudi Arabia: Island Biogeography and Nested Pattern - Mutairi, Khalid Al; Mansor, Mashhor; El-Bana, Magdy; Al-Rowaily, Saud L.; Mansor, Asyraf (IntechOpen, 2012)
None